2015
DOI: 10.1016/j.jad.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and predictors of comorbid bipolar disorder and obsessive–compulsive disorder: A systematic review and meta-analysis

Abstract: This first systematic review and meta-analysis of the prevalence and predictors of comorbid BD-OCD confirms that BD-OCD comorbidity is a common condition in psychiatry with children and adolescents and BD-I patients as the most affected subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 63 publications
8
67
1
5
Order By: Relevance
“…OCD is a comorbid condition in 10%‐20% of patients with BD730, 731, 732, 733 compared with 2%‐3% in the general population 734. However, the prevalence appears to vary widely, depending on the clinical setting and bipolar subtype 731.…”
Section: Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…OCD is a comorbid condition in 10%‐20% of patients with BD730, 731, 732, 733 compared with 2%‐3% in the general population 734. However, the prevalence appears to vary widely, depending on the clinical setting and bipolar subtype 731.…”
Section: Specific Populationsmentioning
confidence: 99%
“…OCD is a comorbid condition in 10%‐20% of patients with BD730, 731, 732, 733 compared with 2%‐3% in the general population 734. However, the prevalence appears to vary widely, depending on the clinical setting and bipolar subtype 731. Comorbid OCD may be more common in children and adolescents with BD than in adults731 and has been reported to co‐occur more commonly with BD than other anxiety disorders,735 although other studies have not found that association 736…”
Section: Specific Populationsmentioning
confidence: 99%
“…7 Also, the nosological status of this comorbidity is less studied. 21 Family studies can be used for a better neurobiological and hence nosological understanding of BD-OCD comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Well-documented demands of efficiency, flexibility, practicality, clinical pertinence and cultural adaptability and applicability have been made regarding both DSM-5 and ICD (73,74). Clinical research with a GMH outreach include themes of integrated care, special populations, risk factors, comorbidities, sub-threshold disorders and "functional im-provement" (75)(76)(77)(78)(79). Epidemiological studies regarding NMS disorders and gap treatments (41), and innovative service provisions of cultural consultations in general hospital settings, cost effectiveness and the institutionalization of use of research findings(80-82) are outstanding contributions.…”
Section: Global Mental Health and Clinical Practicementioning
confidence: 99%